Preparation of Vaccine from Biofilm Proteins of Staphylococcus aureus and Incorporate it in Liposomes for Induction of CXCL-5 Production in Albino Rats - AlKhfaji, Zahraa Abdulrazaq; Darweesh, Mayyada Farhan; Al-Musawi, Ali Fattah (Iraqi Journal of Science, 2024)
In this study biofilm matrix proteins (BMP) were isolated from bacterial biofilm and incorporated in a delivery system (liposome) to stimulate an immune response against virulent pathogens. The specimens were cultured and identified depending on morphological and biochemical tests . Around 67.74% of isolates were found to be biofilm formers. The immunomodulatory activity revealed that BMP-liposome vaccine and BMP vaccine significantly increased chemokine CXCL5 levels in sera of rats in first and second doses. The concentration of total WBCs count, neutrophils, and lymphocytes also increased. In rats groups that had received BMP-liposome vaccine, the challenge test revealed high immunogenicity and effective protection. It can, therefore, be concluded that BMP-liposome are a promising nanomedicine for regulating biofilm hyper-reaction. They may, however, cause tissue inflammation. On the other hand, it appeared to be helpful in activating the immune response at moderate levels, allowing infection to be eradicated without tissue damage.